Perfil epidemiológico de las alteraciones de la oclusión en la población escolar del corregimiento de Genoy, municipio de Pasto, Colombia (2011)
ABSTRACT: The purpose of this study was to determine the prevalence of occlusion alterations in a population of schoolchildren between the ages of 5 and 16 years in the Genoy Township (Pasto), during 2010. Methods: a cross sectional study was conducted in a sample of 439 children at the Institución Educativa Municipal Francisco de la Villota (public school) of the Genoy Township, Municipality of Pasto (Colombia). A clinical exam was carried out and socio-demographic variables, presence of dental caries, arch characteristics, right and left molar relationships for deciduous and permanent teeth, and occlusion alterations were recorded. A descriptive analysis of total frequencies and by gender was conducted. Calculations of prevalence ratios (PR) with 95% confidence intervals (95%CI) were made in order to estimate the association between gender and main occlusion alterations. Results: Caries prevalence was 88%. The occlusion alterations most frequently observed were anterior open bite (10%, more frequent in girls, with no significant differences) and anterior crossbite (9.6%, more frequent in girls, with significant differences, p < 0.05). The most frequent habits were atypical swallowing pattern (38%), pronunciation difficulties (19%) and nail biting (15%). Girls presented Class I molar relationship more frequently than boys. Class II and III molar relationships were observed more frequently in males than in females. Conclusions: some differences in the diagnosis of occlusion alterations were found by gender, being Class I, crossbite and anterior open bite the most common ones in girls. Specific strategies are suggested in order to establish the principal risk factors for these alterations.